Factors associated with dropout from an intradialytic exercise program among patients undergoing maintenance hemodialysis. Issue 4 (14th September 2022) - Yamaguchi, Tomoya; Yabe, Hiroki; Kono, Kenichi; Moriyama, Yoshifumi; Yamada, Tetsuya
ABSTRACT: Background: Continuation of an intradialytic exercise program is necessary to improve and maintain physical function in patients undergoing hemodialysis. Factors associated with dropout must be identified to ensure program continuation. This study aimed to investigate the dropout rates from an intradialytic exercise program at 6 and 12 months in patients undergoing hemodialysis and to identify dropout predictors. Methods: This was a multicenter, retrospective observational study. Overall, 980 patients were enrolled in this study. Grip strength, 10-m walking speed, physical function, demographics and blood sampling data were measured at baseline, and dropouts were observed. Patients were classified as either continued or dropped out of the program at 6 and 12 months. The dropout rate was calculated for each time point. Multivariate logistic regression analysis was performed to identify the predictors of dropout. Results: The dropout rate was 26.4% ( n = 259) after 6 months, 24.1% ( n = 172) between 6 and 12 months, and 44.3% ( n = 424) overall at 1 year. Significant predictors of dropout after 6 months were slower 10-m walking speed, older age and high C-reactive protein level. Predictors of dropout after 12 months were slower 10-m walking speed and lower standardized dialysis volume. Conclusions: Walking capacity, age, inflammation and hemodialysis volume were determinants of dropout from the exercise program. Our findings provide new and important insights into the potential risk factors for dropout from long-term intradialytic exercise programs in patients undergoing hemodialysis.